CD36 Senses Dietary Lipids and Regulates Lipids Homeostasis in the Intestine - Zhao, Lei; Li, Yuqi; Ding, Qiuying; Li, Yanping; Chen, Yaxi; Ruan, Xiong Z. (Frontiers in Physiology, 2021)
Dietary lipids absorbed in the intestine are closely related to the development of metabolic syndrome. CD36 is a multi-functional scavenger receptor with multiple ligands, which plays important roles in developing hyperlipidemia, insulin resistance and metabolic syndrome. In the intestine, CD36 is abundant on the brush border membrane of the enterocytes mainly localized in proximal intestine. This review recapitulates the update and current advances on the importance of intestinal CD36 in sensing dietary lipids and regulating intestinal lipids uptake, synthesis and transport, and regulating intestinal hormones secretion. However, further studies are still needed to demonstrate the complex interactions between intestinal CD36 and dietary lipids, as well as its importance in dietary associated metabolic syndrome.